Inovasi Manajemen Bisnis Syariah Berbasis Ekonomi Biru pada Industri Tambak Udang di Kabupaten Sidoarjo untuk Meningkatkan Daya Saing Global - Syaiful Fadlol Al Mu'arrifn; Lilik Rahmawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores the integration of Islamic business management principles, blue economy concepts, and innovation strategies in the shrimp farming industry of Sidoarjo, Indonesia, to enhance global competitiveness. The research adopts a qualitative approach through literature review and thematic analysis of relevant sources, aiming to formulate a sustainable business model that harmonizes ethical, environmental, and economic dimensions. Findings reveal that applying sharia-based management—including mudharabah and musyarakah contracts, halal certification, and social responsibility through zakat and waqf—creates an equitable business ecosystem. Simultaneously, blue economy practices such as biofloc technology, waste utilization, and mangrove rehabilitation strengthen environmental sustainability and operational efficiency. Additionally, technological innovation through IoT-based monitoring, digital marketing, and traceability systems significantly improves productivity and market access. The synergy of these elements positions Sidoarjo shrimp as a distinctive product with ethical value, sustainability compliance, and premium market potential. This study suggests policy support for sustainable financing, technology adoption, and certification to scale up implementation and recommends future research to quantify its economic and ecological impacts.